RNA fingerprinting using RAP-PCR identifies an EBAF homologue mRNA differentially expressed in rat oviduct - Valdecantos, Pablo Alberto (2004)
As a step towards the identification of genes preferentially expressed in the oviduct during early rat embryo development, we isolated a cDNA fragment (Pr14) by using RNA arbitrarily primed PCR (RAP-PCR), being its expression restricted to oviduct and uterus; its mRNA is mainly expressed in oviduct during late luteal phase and early pregnancy. This fragment is 100% identical to a rat DNA sequence (Accession No. NW_047400) downstream the terminal exon of a Rattus norvegicus gene (Locus Link Accession No. LOC289316) similar to ebaf (endometrial bleeding-associated factor), a novel member of the Transforming Growth Factor superfamily. Northern analyses showed that this sequence hybridizes with 2.9 kb and 4.1 kb mRNAs in early pregnant rat oviducts. However, only the 4.1 kb mRNA was detected in the oviduct of non-pregnant rats, showing an increase from proestrus to diestrus. The expression of this oviduct-uterus specific mRNA suggests that the products of this gene may play a role in the oviductal reproductive process.